In-situ investigations of the inhomogeneous strain on the steel case of 18650 silicon/graphite lithium-ion cells. (20th January 2021) - Wu, Yikun; Zhu, Shengxin; Wang, Zenghui; Zhou, Peijun; Xie, Fuguo; Zhou, Jiang; Chen, Hao-Sen; Song, Wei-Li; Fang, Daining
Abstract: The silicon-graphite composite electrode is the main focus of the high energy and high power density 18650 Li-ion battery cells, while the large volume expansion of the composite electrode may induce the steel case of the cell to deform largely, even rupture. The mechanical reliability of the steel case is very important to the safety and durability of the battery cell. In the paper, the hoop strain of the steel case is in-situ monitored during 18650 Li-ion battery cell operation. At the early cycle stage, the hoop strain of the steel case is induced by the thermal expansion. After a long-term cycle (cycled number > 300 times), inhomogeneous strain distribution, even negative strain, is found on the steel case. Based on the CT images and non-concentric numerical model, it is found that the gap between the jelly roll and steel case is the root of the different hoop strain on the steel case during the cycle. It is suggested that the gap (the diameter ratio of the jelly roll to steel case) need be focused in the engineering design for the cylindrical Li-ion battery cell with next-generation silicon composite electrode. Graphical abstract: Inhomogeneous hoop strain phenomenon on the steel case of the 18650 Li-ion battery cell Image, graphical abstract